2015
DOI: 10.1093/ecco-jcc/jjv188
|View full text |Cite
|
Sign up to set email alerts
|

Azathioprine-induced Acute Pancreatitis in Patients with Inflammatory Bowel Diseases—A Prospective Study on Incidence and Severity

Abstract: Background and Aims:Azathioprine [AZA] is recommended for maintenance of steroid-free remission in inflammatory bowel disease IBD. The aim of this study has been to establish the incidence and severity of AZA-induced pancreatitis, an idiosyncratic and major side effect, and to identify specific risk factors.Methods:We studied 510 IBD patients [338 Crohn’s disease, 157 ulcerative colitis, 15 indeterminate colitis] with initiation of AZA treatment in a prospective multicentre registry study. Acute pancreatitis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
2
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 39 publications
(49 reference statements)
9
82
2
8
Order By: Relevance
“…Regarding the etiology, the most frequent etiologies were postoperative and idiopathic, whereas the frequencies of biliary pancreatitis and post-ERCP pancreatitis were similar (12.5%). In our series, the treatment of IBD in patients having idiopathic acute pancreatitis was also evaluated; none of those patients were treated with azathioprine [13] or mesalazine [14], which have been reported to be causes of acute pancreatitis in IBD patients (probably based on direct toxicity and allergic mechanisms) or in patients with Crohn's disease associated with the blood group B [15] . The results of our study were similar to those previously reported showing that 21% of cases were due to biliary lithiasis, whereas the results of our data regarding idiopathic acute pancreatitis were higher than those previously reported [16,17] .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the etiology, the most frequent etiologies were postoperative and idiopathic, whereas the frequencies of biliary pancreatitis and post-ERCP pancreatitis were similar (12.5%). In our series, the treatment of IBD in patients having idiopathic acute pancreatitis was also evaluated; none of those patients were treated with azathioprine [13] or mesalazine [14], which have been reported to be causes of acute pancreatitis in IBD patients (probably based on direct toxicity and allergic mechanisms) or in patients with Crohn's disease associated with the blood group B [15] . The results of our study were similar to those previously reported showing that 21% of cases were due to biliary lithiasis, whereas the results of our data regarding idiopathic acute pancreatitis were higher than those previously reported [16,17] .…”
Section: Discussionmentioning
confidence: 99%
“…Typical adverse effects of some immunosuppressive substances such as azathioprine are an increased risk for infections and possibly a low risk for lymphoma and non-melanoma skin cancer in the long term [7, 13, 14]. Moreover, there are substance-specific side effects like azathioprine-induced acute pancreatitis [15] or infliximab-associated anaphylactic reactions [16]. …”
Section: Therapy In CD – Goals and Controlsmentioning
confidence: 99%
“…Typical side effects of thiopurines are, for example, fatigue, acute pancreatitis, increased susceptibility for infections and in the long-term potentially lymphoma and non-melanoma skin cancer [8, 32]. The strongest risk factor for azathioprine-induced acute pancreatitis is smoking [15]. Because of convincing data for biologicals, immunomodulators were less frequently used in recent years [32].…”
Section: Approved Substances – State Of the Artmentioning
confidence: 99%
“…Можно предполо-жить, что повышенная активность фермента у носителей генотипа 3404AG может способство-вать усиленной генерации супероксидного ани-онного радикала, развитию окислительного стресса, повреждению митохондрий и таким об-разом способствовать запуску каскада деструк-тивных изменений в поджелудочной железе, вы-званных высвобождением пищеварительных ферментов. Подобный механизм развития острого панкреатита предполагается на фоне лечения аза-тиоприном [12]. В то же самое время ассоциация генотипа 3404AG с повышенным риском разви-тия ХП нами обнаружена только у женщин.…”
Section: результаты исследования и их обсуждениеunclassified
“…Тот факт, что фермент экспрессируется в достаточно большом количестве в клетках поджелудочной железы, свидетельствует о его потенциальной вовлеченности в важнейшие физиологические и патологические процессы в данном органе. При-мечательно, что один из субстратов АОХ1 являет-ся иммунодепрессант азатиоприн -лекарствен-ный препарат, способный провоцировать разви-тие острого панкреатита [3,12].…”
unclassified